A genome-wide association study of gestational diabetes mellitus in Chinese women. (19th May 2021) - Wu, Nan-Nan; Zhao, Dong; Ma, Wei; Lang, Jia-Nan; Liu, Si-Mo; Fu, Ying; Wang, Xin; Wang, Zong-Wei; Li, Qiang
Abstract: Background: Recently, gestational diabetes mellitus (GDM) exhibits an obvious trend of increase in pregnant mothers and usually causes several abnormities or diseases for the offspring. Although several studies have been reported for potential molecular mechanisms, relevant genes or mutated sites have not been intensively investigated in China. Materials and methods: In the present study, 218 pregnant mothers (GDM group: 103 individuals and control group: 115 individuals) in China were enrolled to conduct genome-wide association study (GWAS) and pathway analyses for the purpose of related genes associated with GDM in China. Results: Our results identified 23 SNPs exhibiting closely association with GDM using multiple tests. Annotation of these 23 SNPs identified four genes ( SYNPR, CDH18, CTIF, and PTGIS ), which suggests that the four genes may associate with GDM. GO enrichment and KEGG pathway analysis showed that gene SYNPR, CDH18, and PTGIS were enriched or located into the pathways or process associated with glycometabolism (e.g. insulin resistance and glucose tolerance), which further indicates that the three genes may associate with the GDM. Conclusion: The identification of these potential genes associating with GDM enriched the potential molecular mechanisms of GDM in Asia and will provide abundant stocks for subsequent clinical verifications for better understanding the molecular mechanisms, diagnosis, drug development and clinical treatment of GDM.